Introductory immunology : basic concepts for interdisciplinary applications - Actor, Jeffrey K. (Academic Press, 2023)
Introductory Immunology: Basic Concepts for Interdisciplinary Applications, 3rd Edition, is a completely updated, revised, and expanded concise, conceptual approach to understanding the immune systems as a primary defense to maintain health and homeostasis. This expanded version includes the aspects of microbiology and related immune defense mechanisms important in combating disease, as well critical components related to the field of vaccine development. Immunology as a subject is no longer confined to the realms of "immunology" or "microbiology" studies. Indeed, the subject matter has become increasingly important to understand complex mechanisms found within a wider range of biological systems. This book aims specifically at educated audiences who do not have a deep understanding of medical, biochemical, or cellular knowledge. The overall text will present concepts that portray a comprehensive picture of the natural defenses to infectious agents as well as provide an introduction to mechanisms that lead to autoimmune dysfunction. In addition, immunological diseases will be detailed, with the goal of allowing the readers to gain sufficient knowledge to make sound choices for clinical decisions to affect treatment outcomes. This new edition expands on the existing chapters, focusing on updating the previous text. It has been expanded to include knowledge on effector mechanisms addressing components inherent within cellular responses that are either newly discovered, or missing from the previous edition. It has an extra emphasis on aspects related to mechanisms important in combating microbial agents and critical sections on how vaccines protect against pathogenic invaders to limit associated pathology. The goal is that Introductory Immunology will become the preferred provider of core knowledge in immunology to build a foundation to explore components of the human immune system that work together to confer and understand dysregulation that causes clinical diseases.